Optimization of the potentiometric technique with ion selective electrode for evaluating sulfate ion in aqueous samples - Cubillán, Dalia; Núñez, Neida; González, Graciela; Camargo, Nuris (Rev. Téc. Fac. Ing. Univ. Zulia)
Véase archivo PDF